2020
DOI: 10.3390/plants9080952
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Pigeonpea (Cajanus cajan (L.) Millsp.) Genotypes for Zinc Efficiency

Abstract: Pigeonpea (Cajanus cajan (L.) Millsp.) is grown globally for its protein-rich seed. However, low availability of soil zinc (Zn) adversely affects the seed yield of pigeonpea. The present study was therefore conducted to assess the Zn efficiency of pigeonpea genotypes based on seed yield and seed Zn uptake efficiency. Field experiments were conducted at the Indian Council of Agricultural Research–Indian Institute of Soil Science, Bhopal, India with twenty different pigeonpea genotypes and two levels of Zn appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(36 reference statements)
5
13
0
Order By: Relevance
“…To enhance the variability for Fe and Zn in the primary gene pool, Sharma et al (2020) attempted interspecific crosses with Cajanus platycarpus . Despite this, a good response to agronomic biofortification for Fe and Zn was reported in pigeonpea ( Gopalakrishnan et al, 2016 ; Hanumanthappa et al, 2018 ; Behera et al, 2020 ). However, Upadhyaya et al (2010) identified 14 high Zn accessions from core and mini-core collections of pigeonpea available in Genebank at ICRISAT, India.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the variability for Fe and Zn in the primary gene pool, Sharma et al (2020) attempted interspecific crosses with Cajanus platycarpus . Despite this, a good response to agronomic biofortification for Fe and Zn was reported in pigeonpea ( Gopalakrishnan et al, 2016 ; Hanumanthappa et al, 2018 ; Behera et al, 2020 ). However, Upadhyaya et al (2010) identified 14 high Zn accessions from core and mini-core collections of pigeonpea available in Genebank at ICRISAT, India.…”
Section: Discussionmentioning
confidence: 99%
“…However, the trend across three harvests was similar for Aliyu‐Amba and Hawassa, but a different trend was observed at Wondo‐Genet. The variability among locations might be attributed to the rainfall and temperature of the locations (Mishra et al., 2017) and the physico‐chemical characteristics of the soil (Behera et al., 2020). The effect of IPS was not consistent across locations.…”
Section: Discussionmentioning
confidence: 99%
“…Significant genotypic differences for Zn efficiency have been observed in many crop species, such as rice (Oryza sativa) [20.21], wheat It is well known that if researchers can identify crop traits that improve Zn efficiency, growers could have improved yields in Zn-poor soils worldwide. Significant genotypic differences for Zn efficiency have been observed in many crop species, such as rice (Oryza sativa) [20.21], wheat (Triticum aestivum) [9], common beans (Phaseolus vulgaris) [10], maize (Zea mays) [22], sorghum (Sorghum bicolor) [23], soybeans (Glycine max), tomatoes (Solanum lycopersicum) [24], chickpeas (Cicer arietinum) [18,19], barley (Hordeum vulgare) [25], and pigeon peas (Cajanus cajan) [26]. There is increasing importance for Zn-efficient cultivars that could adapt to and cope with low-Zn soils.…”
Section: Evidence Of Natural Genetic Variation For Plant Zn Efficiency: a Large Untapped Resource For Overcoming Low-zn Stressmentioning
confidence: 99%